Practice theory and conservative thought. (December 2019) - Strand, Michael
The concept of practice is thematically central to modern conservative thought, as evident in Edmund Burke's writings on the aesthetic and his diatribe against the French Revolution. It is also the main organizing thread in the framework in the human sciences known as practice theory, which extends back at least to Karl Marx's 'Theses on Feuerbach'. This article historicizes 'practice' in conservative thought and practice theory, accounts for the family resemblance between the two, and takes apart that family resemblance to reveal differences. The ingredients of practice theory (historical inheritance, embodiment, cognitive limits, loose coupling between conscious thought and action) are in many cases also distinctive traits of conservative thought. But the similarity is deceptive. Practice theory and conservative thought constitute two distinct interpretations of practice, two disparate endeavours for connecting human science with political strategy, and two different formulas for opposing theory and practice. The present study will argue that this is primarily a political opposition for conservative thought, while it is a human-scientific opposition for practice theory. Conservative thought is initially political and then human-scientific; practice theory is initially human-scientific and then political. This article advocates for practice theory against conservative thought as differently amended versions of a politics that recognizes human finitude.